Constituição Comunicativa da Reputação Corporativa Contestada (CCRCC): Um estudo das narrativas de empresas com atuação nacional e regional e das contranarrativas dos stakeholders - Santos, Thaís Moura Martins dos (2024)
Contextualization: in certain sectors, corporate reputation is being challenged by the demand for other, more responsible and society-oriented practices and actions. Corporate reputation refers to how an organization is perceived by its stakeholders over time. In a connected world, organizations do not have full control over their reputation; however, they can use corporate communication to influence how they are judged and evaluated. The perspective of Organizational Communicative Constitution (CCO) presupposes that communication is the means through which organizations are established and sustained. From an interpretivist and constructionist epistemological perspective, this research establishes a dialogue between Corporate Reputation (RC) studies and CCO. Objective: considering that corporate reputation can be contested, meaning questioned by the public, the research aims to analyze the macro-narratives of companies with contested corporate reputations from the perspective of CCO, and the counter-narratives of their stakeholders. The research problem is: how is corporate reputation communicatively constituted by organizational narrative strategies employed by companies that have their corporate reputation contested due to instances of reflexive ruptures and counter-narratives from their stakeholders? Method: the qualitative approach and narrative research method guide the collection and analysis of the research material. In the first stage of data collection, aspects of corporate reputation contestation are described for companies operating nationally and regionally across various sectors of the economy: Coca-Cola, Bayer, BAT, BRF, BP Bunge, and LD Celulose. In the second stage, the corporate narratives of these companies on their websites and on social media platform X (Twitter) were analyzed. In the third stage, the counter-narratives of stakeholders—publics who are key figures in contesting the corporate macro-narratives—were analyzed through publications on the studied organizations' own websites, posts and comments on social media platform X, scientific articles, publications from governmental bodies, news reports, and legislation. Results: the analysis of various themes/situations of contestation among the researched companies showed that these firms employ strategies to repair their corporate reputation through narratives published on their websites and social media platform X. However, these narratives may omit relevant information about the theme/situation, as well as confuse, deceive, and even persuade stakeholders. The analysis of corporate narratives identified seven new strategies for repairing corporate reputation, in addition to those already present in the literature: (1) Presentation of scientific evidence, (2) Commitment to society, (3) Compliance with legislation, (4) Reversal of the offensive act, (5) Regret, (6) Acknowledgment of the offensive act and (7) Denunciation of the offensive act. In the literature on counter-narratives, a widely disseminated typology was not found. The analysis of stakeholders' counter-narratives identified nineteen types: (1) Accusation, (2) Analogy, (3) Approval, (4) Commitment to society, (5) Awareness, (6) Criticism, (7) Compliance with legislation, (8) Denunciation, (9) Dissemination, (10) Clarification, (11) Oversight, (12) Inspiration, (13) Economic interest, (14) Irony/humor, (15) Omission, (16) Court order, (17) Scientific perspective, (18) Commercial restriction and (19) Technique. From the analysis of these three elements—theme/episode of contestation, organizational narratives, and stakeholders' counter-narratives—the concept of Communicative Constitution of Contested Corporate Reputation (CCRCC) was proposed. CCRCC assumes that organizations, facing continuous or episodic crises of corporate reputation, employ different narrative strategies to address the contested issues of their reputation and the strategies of stakeholders' counter-narratives. Compliance of the research with the PPGAdm concentration area (Regionality and Management) and with the research line: the CCO, along with other studies, advocates for the return of linguistics in organizational management studies. The dialogue between the CCO perspective and contested corporate reputation studies leads to the proposition of a new theoretical concept for the field of organizational management: the Communicative Constitution of Contested Corporate Reputation (CCRCC)." Impact and Innovation: this thesis innovates by proposing the integration of CCO and the concept of Contested Corporate Reputation of companies operating nationally and regionally; by analyzing that Contested Corporate Reputation is countered by various stakeholders of the researched companies through counter-narratives, seen as communicative practices constitutive of corporate reputation; and by introducing the concept of Contested Corporate Reputation (RCC): the outcome of corporate narratives and stakeholders' counter-narratives of an organization. Economic, Social, and Regional Impact: the results of this study can support companies' strategic decisions regarding corporate communication of their practices, products, and processes, and in understanding the interdependence between corporate macro-narratives and stakeholders' counter-narratives during episodic and continuous corporate reputation crises. In terms of social impact, the research raises awareness among the general public about the different communication strategies used by companies with contested reputations and about the possible counter-arguments used to demand more responsible corporate behavior. It highlights that active participation of stakeholders, individually or in groups, can promote changes in organizational practices. The regional impact is linked to prioritizing the study of themes and episodes of contestation related to large companies operating nationally, internationally, and regionally, with a focus on the Triângulo Mineiro and Sul de Goiás regions. This provides a direct contribution to the communities in these specific regions. Regional Implications: national scope contentious issues such as sugar in soft drinks (Coca Cola), OGM’s (Bayer-Monsanto), and e-cigarettes (BAT) received greater online media coverage and were more discussed on social media platform X than regional scope contentious situations like labor rights violations (BRF), forced labor (BP), and pollution of the Araguari River (LDC). This can be explained by the fact that episodes that may generate local or regional contention are not widely reported and thus their impact is not as widely understood, debated, and questioned compared to national themes/episodes. This implies that the pressure exerted on companies is lower and they may even evade responsibility for the offensive act, as observed in BRF's repeated violations of labor rights, where the company issued only two brief responses. The only exception observed was the episode of slavery-like labor (BP), which despite being regional had extensive media coverage and led to serious corporate reputation contention for BP, perhaps due to the nature of the episode itself where the degrading working conditions of those workers shocked and outraged the general public. Sustainable Development Objectives: his research addressed the following SDGs with their respective themes/episodes of contention: SDG 2 - End hunger, achieve food security and improved nutrition and promote sustainable agriculture. Goal 2.5 By 2020, maintain the genetic diversity of seeds, cultivated plants and farmed and domesticated animals and their related wild species, including through soundly managed and diversified seed and plant banks at the national, regional and international levels, and promote access to and fair and equitable sharing of benefits arising from the utilization of genetic resources and associated traditional knowledge, as internationally agreed. (Discussion about Bayer's transgenic seeds) SDG 3 – Ensure healthy lives and promote well-being for all at all ages. Goal 3.a Strengthen the implementation of the World Health Organization Framework Convention on Tobacco Control in all countries, as appropriate. (Discussion about electronic cigarettes and the company BAT) SDG 6 – Ensure availability and sustainable management of water and sanitation for all. Goal 6.3 By 2030, improve water quality by reducing pollution, eliminating dumping and minimizing release of hazardous chemicals and materials, halving the proportion of untreated wastewater and substantially increasing recycling and safe reuse globally. (Discussion about the pollution of the Araguari river by the LD Celulose factory) SDG 8 - Promote sustained, inclusive and sustainable economic growth, full and productive employment and decent work for all. Goal 8.7 Take immediate and effective measures to eradicate forced labour, end modern slavery and human trafficking and secure the prohibition and elimination of the worst forms of child labour, including recruitment and use of child soldiers, and by 2025 end child labour in all its forms. (Discussion about work analogous to slavery and the episode involving BP Bunge) Goal 8.8 Protect labour rights and promote safe and secure working environments for all workers, including migrant workers, in particular women migrants, and those in precarious employment. (Discussion about non-payment of overtime to employees by BRF).